DEATH RITUALS IN THE DESERT (ROHI): AN INTRODUCTORY AND ISLAMIC REVIEW - Dr. Hafiz Nasir Ali; Muhammad Zubair Madni (Journal of Religion and Society, 2025)
It is a clear fact that any act of any person comes into existence on the basis of an ideology, a belief, a thought, and these sayings of individuals take the form of customs and traditions with the passage of time and when a man deviates from them, the society taunts him as a rebel. If a correct and transparent system of thought is not cultivated by demolishing these false palaces of rituals and customs based on corrupt ideas and wrong beliefs, then the society cannot be corrected till then. Since the Rohi civilization is an ancient civilization, like other civilizations, it also has its own social customs and traditions. Rituals on occasions of grief are characteristic of the culture here, Islam is a religion of nature and a religion of great simplicity, due to social mixing, there is a cloud on these Islamic teachings, it is necessary to remove this cloud and put it in the Islamic sieve. These customs and traditions should be examined and presented and it should be told what is permissible and what is not permissible. Keywords: Rituals, ideology, traditions, Rohi, culture.